Holoprosencephaly or severe hydrocephalus: T1 sequence tells the story. Issue 5 (8th May 2019) - Zarei, Fariba; Iranpour, Pooya; Haseli, Sara
Abstract : Intracranial lipoma is a relatively rare benign lesion. Many are incidental findings; however, some others may present with headache, hydrocephalus or other neurological symptoms; thus, correct diagnosis of this condition is important. These lesions are of high signal intensity on T2-weighted MRI and especially those close to cerebrospinal fluid (CSF) spaces, can easily be overlooked in the background of high signal intensity of CSF. Here, we present a case of tectal lipoma, with subsequent severe hydrocephalus and absence of septum pellucidum which was initially misinterpreted as a form of holoprosencephaly, due to inadequate attention to T1-weighted images.